Differential Europeanization? Explaining the impact of the early warning system on subnational parliaments in Europe. Issue 2 (2nd December 2015) - Borońska-Hryniewiecka, Karolina
Abstract : The inclusion of subnational parliaments into the early warning system (EWS) for subsidiarity control generates transforming dynamics in parliamentary modus operandi in European Union (EU) decentralized states. Empirical findings reveal considerable variations in the pace and scope of subnational parliamentary activity in EU policy control challenging the existing theories of territorial mobilization. Drawing from a comparative institutional analysis, this article offers a theoretical framework that permits accounting for cross-country variations in subnational parliamentary mobilization in EU affairs, under the EWS. By placing an increased focus on the domestic environment, it suggests that the two important factors which might affect the scope of parliamentary activity are (1) the relationship between the executive and legislature at the subnational level, and (2) the position of the regional executive in domestic governance arrangements.